Tinjauan Corporate Social Responsibility pada KPP Pratama Palembang Seberang Ulu - Okta Ana Reza; Septiani Fransisca (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This study aimed to review the implementation of Corporate Social Responsibility (CSR) at KPP Pratama Palembang Seberang Ulu as a form of social responsibility of government agencies towards the community. The methods used in this study are observation, interviews and documentation during the internship activities. The results of this study indicated that the implementation of CSR at KPP Pratama Palembang Seberang Ulu has been running well and reflects the application of the Triple Bottom Line concept (people, planet, profit) through various activities, such as tax socialization, blood donation, donations to orphanages and ederly social homes, and tree planting.